Changing varicella epidemiology in active surveillance sites--United States, 1995-2005 - Guris, Dalya; Jumaan, Aisha O; Mascola, Laurene; Watson, Barbara M; Zhang, John X; Chaves, Sandra S; Gargiullo, Paul; Perella, Dana; Civen, Rachel; Seward, Jane F (The Journal of infectious diseases, 2008)
Significant reductions in varicella incidence were reported from 1995 to 2000 in the varicella active surveillance sites of Antelope Valley (AV), California, and West Philadelphia (WP), Pennsylvania. We examined incidence rates, median age, and vaccination status of case patients for 1995-2005. Coverage data were from the National Immunization Survey. By 2005, coverage among children 19-35 months of age reached 92% (AV) and 94% (WP); 57% and 64% of case patients in AV and WP, respectively, were vaccinated; and varicella incidence declined by 89.8% in AV and 90.4% in WP. Incidence declined in all age groups, especially among children <10 years of age in both sites and among adolescents 10-14 years of age in WP. In AV, since 2000, the incidence among adolescents 10-14 and 15-19 years of age increased. Implementation of school requirements through 10th grade in WP may explain the differences in the decline in incidence among adolescents. Continued surveillance will be important to monitor the impact that the 2-dose vaccine policy in children has on varicella epidemiology.